Impact of medication nonadherence on stroke recurrence and mortality in patients after first‐ever ischemic stroke: Insights from registry data in Singapore. Issue 5 (19th March 2020) - Yeo, See‐Hwee; Toh, Matthias Paul Han Sim; Lee, Sze Haur; Seet, Raymond Chee Seong; Wong, Lai Yin; Yau, Wai‐Ping
Abstract: Purpose: This retrospective cohort study aims to examine adherence to secondary stroke preventive medications and their association with risk of stroke recurrence and mortality in patients after first‐ever ischemic stroke. Methods: Using data from the National Healthcare Group and Singapore Stroke Registry, patients with first‐ever ischemic stroke between 2010 and 2014 were included, and categorized based on antithrombotic or statin adherence using the proportion of days covered: high (≥75%), intermediate (50%‐74%), low (25%‐49%), and very low (<25%). The primary outcome was first recurrent ischemic stroke within a year after hospital discharge, while the secondary composite outcomes were (a) stroke recurrence and all‐cause mortality and (b) stroke recurrence and cardiovascular mortality. The Cox proportional hazard model was used to examine the association between medication adherence and outcomes. Adjusted hazard ratios (aHRs) and the corresponding 95% confidence intervals (CIs) were reported. Results: Among ischemic stroke patients prescribed with antithrombotics (n = 1139) or statins (n = 1160) at hospital discharge, about one‐third were highly adherent to their medications. Patients with lower medication adherence tended to be younger, were admitted to private ward classes, and were without hypertension. Compared with the patients with high medication adherence, the risk of stroke recurrence was higher in patients with very low antithrombotic (aHR = 4.65; 95% CI: 1.45‐14.89) or statin (aHR = 3.44; 95% CI: 0.93‐12.74) adherence. Similar findings were observed for the secondary outcomes. Conclusions: Poor adherence to antithrombotic and statin treatment increases the risk of recurrent stroke and mortality in patients after first‐ever ischemic stroke. Further measures are needed to improve medication adherence among stroke survivors.